Indigenous knowledge dissemination and use: a discuss (2008)
The paper discusses the dissemination and use of indigenous knowledge. It highlighted the type and sources of indigenous knowledge in Nigeria. Means and tools for creating and exchanging indigenous knowledge, the likely situations under which indigenous knowledge could be used and how indigenous knowledge can be disseminated were discussed. The paper concluded by making recommendations on how to promote the creation, usage and transfer of indigenous knowledge in Nigeria.